The Impact of Brand Equity and Promotion on Toyota Customer Loyalty at the "XYZ" Dealership in Surabaya City - Istanti, Enny; Kristiawati, Indiana; Daengs GS, Achmad (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: to find out how the influence of brand equity and promotion on Toyota consumer loyalty at the "XYZ" Surabaya dealership Design/methodology/approach: The method of data processing and analysis is using quantitative analysis which includes the interpretation of data obtained in research and the results of data processing that has been carried out by providing information and explanations, as well as quantitative analysis which includes validity and reliability tests, multiple regression analysis, hypothesis tests through F test and T test and regression coefficient analysis (R2). Findings: the influence of brand equity and promotion has a good influence on customer loyalty. Based on the results of the analysis, the indicators in this study are valid and the variables are reliable. The results of this study show that there is a simultaneous influence on brand equity and promotion variables on customer loyalty. The results of this study also show that brand equity and promotion variables have a significant partial effect on customer loyalty. In the determination test, there was an influence of 60.5% of the independent variables (brand equity and promotion) on the dependent variable (customer loyalty). Meanwhile, the remaining 39.5% were influenced by other variables and were not included in this study. Practical implications: knowing the effect of brand equity and promotion on Toyota consumer loyalty at the "XYZ" Surabaya dealership Originality/value: This paper is original Paper type: research paper